The value of serum IL-4 to predict the survival of MDS patients - Zhaoyun Liu; Xintong Xu; Likun Zheng; Kai Ding; Chun Yang; Jincheng Huang; Rong Fu (European Journal of Medical Research, 2023)
Abstract Background Immune indicators are routinely used for the detection of myelodysplastic syndrome (MDS), but these are not utilized as a reference indicator to assess prognosis in MDS-related prognostic evaluation systems, such as the World Health Organizational prognostic scoring system, the international prostate symptom score, and the revised international prostate symptom score. Methods We examined immune indicators, including cluster of differentiation (CD)3, CD4, CD8, CD56, CD19, interleukin (IL)-2, IL-4, IL-6, IL-10, tumor necrosis factor-a, and interferon-γ in 155 newly diagnosed MDS patients. We also conducted a correlation analysis with clinical indices. Results IL-4 was found to be a predictor of survival in these 155 patients using the receiver operating characteristic curve, with 5.155 as the cut-off point. Patients with serum IL-4 levels ≥ 5.155 had a lower overall survival (OS) than those with IL-45.155 at diagnosis. Furthermore, multivariate analysis revealed that IL-4 levels > 5.155 were an independent predictor of OS (hazard ratio: 0.237; 95% confidence interval, 0.114–0.779; P = 0.013). In addition, serum IL-4 expression in the three different scoring systems showed significant differences in the survival of medium- to high-risk MDS patients (P = 0.014, P < 0.001, P < 0.001). Conclusions According to our study, IL-4 levels at the time of diagnosis can predict MDS prognosis in patients as a simple index reflecting host systemic immunity.